Kemampuan Seni Rupa Teknik Pengecapan Pada Anak Tunagrahita Menggunakan Metode Demonstrasi Di SLBS Fajar Amanah - Sriana Sriana (Lembaga Pengembangan Kinerja Dosen, 2024)
The content of learning in children with intellectual disabilities is prioritized in the aspect of skills, but the ability of fine arts of children with intellectual disabilities, especially in learning taste, has not been maximized. This is coupled with the learning methods used by teachers are not quite right. This study aims to describe the fine art skills of tungrahita children with tasting techniques using demonstration methods. This study used an experimental research design with a one group pretest and post-test design. Based on the results of the analysis, the probability value of the sample results is 0.0010 < α (0.05) so that H0 is rejected. So it can be concluded that the demonstration method affects the ability to create fine art, collage techniques in children with intellectual disabilities.